Incidence of Infections and Predictors of Mortality During Checkpoint Inhibitor Immunotherapy in Patients With Advanced Lung Cancer: A Retrospective Cohort Study. (13th April 2021) - Bavaro, Davide Fiore; Pizzutilo, Pamela; Catino, Annamaria; Signorile, Fabio; Pesola, Francesco; Di Gennaro, Francesco; Cassiano, Sandro; Marech, Ilaria; Lamorgese, Vito; Angarano, Gioacchino; Monno, Laura; Saracino, Annalisa; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) have revolutionized nonsmall cell lung cancer (NSCLC) treatment and significantly increased overall survival of patients. However, the incidence of concurrent infections and their management is still debated. Methods: From August 2015 to October 2019, all consecutive patients with NSCLC who received nivolumab or pembrolizumab as first- or second-line therapy were retrospectively evaluated. At the time of analysis all patients had died. Clinical characteristics of patients, type of infections, and predictors of mortality were analyzed. Results: A total of 118 patients were identified: 74 in the nivolumab group and 44 in the pembrolizumab group. At least 1 infection was recorded in 22% of the nivolumab-group versus 27% of the pembrolizumab-group ( P = .178). In both groups, the main infection was pneumonia, followed by skin and soft tissue infections, urinary tract infections, and gastroenteritis. Crude mortality for first infection was 10.7%, followed by 25% and 40% for the second and third recurrence, respectively (p for trend = .146). No opportunistic infections were recorded. It is notable that, by Cox-regression model, the independent predictor of mortality was a higher Eastern Cooperative Oncology Group performance status at baseline ( P < .001), whereas the multidisciplinary diagnosis and treatment of concurrent infections was associated with a reduced probability of mortality (adjusted hazard ratio = 0.50; 95% confidence interval = 0.30–0.83; P < .001). Conclusions: In patients with NSCLC treated with ICIs, multidisciplinary management of concurrent infections may reduce the risk of mortality. Further studies to investigate risk factors for infections, as well as appropriate management strategies and preventive measures in this setting, are warranted. Abstract : Immune checkpoint inhibitors have revolutionized non–small cell lung cancer treatment. In these patients, multidisciplinary management of concurrent infections with Infectious Diseases specialists may reduce the risk of mortality. Further studies to investigate risk factors for infections are warranted.